Natural vs. anthropogenic sources supply aeolian dust to the Miaoergou Glacier: Evidence from Sr–Pb isotopes in the eastern Tienshan ice core. (12th February 2017) - Du, Zhiheng; Xiao, Cunde; Liu, Yaping; Yang, Jiao; Li, Chuanjin
Abstract: The compositions of Sr and Pb isotopes in the soluble and insoluble dust in six samples from the Miaoergou ice core in eastern Tienshan, China, were measured. The six samples were dated from top to bottom as follows: 2000 AD, 1991 AD, 1983 AD, 1977 AD, 1962 AD and 1958 AD. The 87 Sr/ 86 Sr ratios in the soluble fraction ranged from 0.709984 to 0.711031. The isotopic ratios of Pb in the soluble and insoluble dust were between 17.962–18.182 and 18.198–18.409 for 206 Pb/ 207 Pb; 15.540–15.606 and 15.560–15.581 for 208 Pb/ 207 Pb; and 37.994–38.173 and 38.179–38.384 for 208 Pb/ 204 Pb, respectively. These isotopic results for insoluble dust allowed us to document the origins of the dust in the Miaoergou Glacier in eastern Tienshan. The major sources of the natural aeolian deposits were the Taklamakan and Gobi deserts. Natural and anthropogenic Pb sources were assessed using a simple ternary model in which deserts, lead ore and coal served as the primary sources of insoluble dust. Lead ore, coal combustion, and the use of leaded gasoline in the surrounding area may represent additional anthropogenic sources of soluble dust. Thus, anthropogenic sources could be further investigated by using the dust-free soluble fractions. The Pb concentration and Pb isotopic compositions from the High Asia ice cores provided distinct evidence of the positive influences of anthropogenic factors associated with industrial development and the prevailing atmospheric circulation patterns in these regions.